The impact of TP53 and PTEN tumor suppressor genes on response to different breast cancer treatment modalities - Nikola Tanić; Tatjana Dramićanin; Nejla Ademović; Tijana Tomić; Blagoje Murganić; Zorka Milovanović; Milica Nedeljković; Nasta Tanić (Биомедицинска истраживања, 2022)
Introduction: Breast cancer (BC) is the most frequent type of malignancy and the leading cause of cancer related death among women worldwide. BC is exceptionally heterogeneous disease and therefore distinct treatment modalities are necessary to address these differences. The aim of our study was to investigate the impact of TP53 and PTEN tumor suppressor genes (TSGs) inactivation on BC response to different treatment modalities and their possible cooperation, on post-operative BC samples. Methods: Patients were classified, based on applied adjuvant therapy, into four distinct groups: those that received hormonal therapy (HT) only, hormonal therapy combined with chemotherapy (HT/CHT), hormonal therapy combined with chemo and biological therapy (HT/CHT/H), and other systemic therapies that exclude HT. Functional inactivation of TP53 and PTEN TSG’s were studied by mutation, loss of heterozygosity (LOH) and hypermethylation analysis. Results: Our results revealed that TP53 gene was altered in 63 out of 90 specimens (70%), while the frequency of PTEN alterations was slightly lower, 54 out of 90 (60%). Simultaneous inactivation was detected in 43 tested samples (48%) with significant association between two analyzed TSGs. Further, we found that TP53 status has significant influence on patients’ therapy response. Contrary to this, no significance was found between mutational status of PTEN and various treatment modalities. However, significant association was found between the type of applied therapy and simultaneous alterations of these two TSGs (p = 0.00001). Conclusion: Patients with wtTP53 show significantly better therapy response regardless of the type of therapy, compared to carriers of altered TPp53 gene.
Keywords: breast cancer; p53; PTEN; adjuvant therapy